Rehabilitation Framework for HIV/AIDS Clients in the Public Health Field Practice of Nursing Students: A Case Study - Sukatemin; Budi Joko Santosa; Zakirullah Zakirullah; Syaifoel Hardy (Science Midwifery, 2022)
One of the phenomena of people living with HIV/AIDS in the rehabilitation phase in rural areas is that there is not enough space for them to get optimal rehabilitation services. The objective of this study was to provide a public health field practice framework for nursing students in the rehabilitation of people with HIV/AIDS. This research used a case study with a collective design. The primary data were taken from in-depth interviews of 3 informants. Secondary data was from reputable journals. Data processing was done by organizing, sorting, grouping, coding, marking, and categorizing based on specific groupings. The analysis used descriptive analysis. The study found three problems i.e. HIV/AIDS material is in the curriculum, public health field practice is held in semester 5, and no specific guidelines for public health practice programs on the rehabilitation of HIV/AIDS. This study recommended student interventions in the rehabilitation framework for people with HIV/AIDS referring to public health field practices based on the 2019 National Guidelines for HIV/AIDS Management.